The archaeology of North Pacific fisheries - Moss, Madonna; Cannon, Aubrey (University of Alaska Press, 2011)
For thousands of years, fisheries were crucial to the sustenance of the First Peoples of the Pacific Coast. Yet human impact has left us with a woefully incomplete understanding of their histories prior to the industrial era. Covering Alaska, British Columbia, and Puget Sound, The Archaeology of North Pacific Fisheries illustrates how the archaeological record reveals new information about ancient ways of life and the histories of key species. Individual chapters cover salmon, as well as a number of lesser-known species abundant in archaeological sites, including pacific cod, herring, rockfish.